IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION THROUGH BUSINESS PLAN FOR STUDENT CHARACTER BUILDING - Rokhmawati, Isnaini; Tinus, Agus; Wurianto, Arif Budi (Universitas Labuhanbatu, 2025)
Purpose - This study aims to analyze and evaluate the implementation of entrepreneurship learning through a business plan to shape the entrepreneurial character of students at SMK. The expected entrepreneurial character includes creativity, independence, courage to take risks, responsibility, and perseverance.Methodology - The approach in this study is qualitative, supported by descriptive data, and data collection using interview techniques, consisting of the principal, head of department, entrepreneurship teacher, and travel business expertise program department students. The data analysis technique uses the Miles and Huberman approach including data reduction, data display, and conclusion.Findings - The study results indicate that applying a business plan in entrepreneurship learning can strengthen students' understanding of the entrepreneurial process systematically and in a planned manner. In addition, this learning significantly increases students' motivation and confidence to start an independent business. This entrepreneurship learning through business plans has proven effective in shaping students' entrepreneurial character, preparing them for challenges in the world of work, and opening up opportunities to become competent young entrepreneurs.Cintribution - This study provides scientific facts about entrepreneurship learning through business plans as an effort to shape students' entrepreneurial character, through data collected by researchers, so that it can be used as a reference and consideration for policies that will be taken, both in improving instructor skills and developing more contextual learning modules to support the success of entrepreneurship programs in vocational schools